Effect of COVID-19 pandemic on older adults’ emotion regulation and quality of life after lockdown in Italy - Pezzuti, Lina; Figus, Monica; Lauriola, Marco (Psychology Hub, 2021)
After SARS and MERS, COVID-19 was the third pandemic caused by the coronavirus that generated panic worldwide. Therefore, the negative impact of COVID-19 on mental health among the general population has been identified as a research priority. Despite this, some studies suggest that the elderly population is underrepresented. The present research aimed to compare the emotional regulation and the quality of life of a group of 150 elderly assessed during the pandemic isolation for COVID-19 with the normative data of a group of pre-COVID-19 elderly. Another aim is to study the relationship between emotional regulation, perceived acute stress, quality of life, and risk perception with the variables age, years of education, gender, and cohabitation status of elders assessed during the pandemic isolation for COVID-19. The results showed that: the elders assessed during the Covid period had a lower capacity for emotional regulation; compared to younger people, older people were less capable of emotional regulation, had a higher perceived risk of COVID-19 infection, and were less satisfied with their independence; higher levels of education reflected a greater capacity for emotional regulation; women showed a lower capacity for emotional regulation and higher stress and perceived risk; the elders who lived alone seemed to be more vulnerable than who lived with other people. The findings underscore the need to assess the psychological effects of the pandemic in the elderly population, particularly for the most vulnerable individuals.